The Economic Thought in Christian Middle Ages – Part 2 - Rothbard, Murray N. (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2013)
The author presents the development of economic thought in the Middle Ages (twelfth and thirteenth centuries), giving attention primarily to the understanding of canonists and theologians of the great medieval universities and the great thinkers of emerging religious orders such as Dominicans and Franciscans, to economic aspects as usury, collection of interest and the establishment of “just price”.